Hepatocyte and stellate cell deletion of liver fatty acid binding protein reveals distinct roles in fibrogenic injury. Issue 3 (21st December 2018) - Newberry, Elizabeth P.; Xie, Yan; Lodeiro, Carlos; Solis, Roberto; Moritz, William; Kennedy, Susan; Barron, Lauren; Onufer, Emily; Alpini, Gianfranco; Zhou, Tianhao; Blaner, William S.; Chen, Anping; et al.
ABSTRACT: Liver fatty acid binding protein (L‐Fabp) modulates lipid trafficking in enterocytes, hepatocytes, and hepatic stellate cells (HSCs). We examined hepatocyte vs . HSC L‐Fabp deletion in hepatic metabolic adaptation and fibrotic injury. Floxed L‐Fabp mice were bred to different transgenic Cre mice or injected with adeno‐associated virus type 8 (AAV8) Cre and fed diets to promote steatosis and fibrosis or were subjected to either bile duct ligation or CCl4 injury. Albumin‐Cre‐mediated L‐Fabp deletion revealed recombination in hepatocytes and HSCs; these findings were confirmed with 2 other floxed alleles. Glial fibrillary acid protein‐Cre and platelet‐derived growth factor receptor β‐Cre‐mediated L‐Fabp deletion demonstrated recombination only in HSCs. Mice with albumin promoter‐driven Cre recombinase (Alb‐Cre)‐mediated or AAV8‐mediated L‐Fabp deletion were protected against food withdrawal‐induced steatosis. Mice with Alb‐Cre‐mediated L‐Fabp deletion were protected against high saturated fat‐induced steatosis and fibrosis, phenocopying germline L‐Fabp −/− mice. Mice with HSC‐specific L‐Fabp deletion exhibited retinyl ester depletion yet demonstrated no alterations in fibrosis. On the other hand, fibrogenic resolution after CCl4 administration was impaired in mice with Alb‐Cre‐mediated L‐Fabp deletion. These findings suggest cell type‐specific roles for L‐Fabp in mitigating hepatic steatosis and in modulating fibrogenic injury and reversal.—Newberry, E. P., Xie, Y., Lodeiro, C., Solis, R., Moritz, W., Kennedy, S., Barron, L., Onufer, E., Alpini, G., Zhou, T., Blaner, W. S., Chen, A., Davidson, N. O. Hepatocyte and stellate cell deletion of liver fatty acid binding protein reveal distinct roles in fibrogenic injury. FASEB J. 33, 4610–4625 (2019). www.fasebj.org